Local Organizations Supporting Implementation of Graphic Health Warnings for Tobacco in Underserved Communities: A Qualitative Inquiry - Ramanadhan, Shoba; Nagler, Rebekah H.; Alexander-Molloy, Jaclyn M.; Viswanath, Kasisomayajula (Frontiers in Public Health, 2018)
Background: Graphic health warnings (GHWs) on cigarette packages offer the potential to support tobacco cessation and prevention of initiation. Guidance for supporting implementation at the local level is limited, which can lead to missed opportunities to amplify the health impact of GHWs. This study examines the potential for local organizations engaged in tobacco control in underserved communities to support GHW implementation. Materials and Methods: Key informant interviews were conducted with 20 leaders in the three partner communities of Boston, Lawrence, and Worcester, Massachusetts. Data were analyzed using a combination of inductive and deductive methods, grounded in a framework analysis approach. Results: First, participants expected local organizations to play a diverse range of roles to support GHW policy implementation, ranging from convening local actors to offering complementary health education activities. Second, there is a need for external agencies to actively support local organizations during the pre-implementation and implementation phases, e.g., by engaging local organizations and providing resources and technical assistance. Finally, participants noted concerns about potential disconnects between the GHWs and the needs of underserved populations. Discussion: With the necessary supports, local community organizations can be important implementation partners to maximize the impact of GHWs and ensure that benefits accrue to members of underserved communities.